THE INFLUENCE OF EMPLOYEE EXPERIENCE, EMPLOYEE ENGAGEMENT, AND WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE AT PT. PUPUK ISKANDAR MUDA NORTH ACEH - Yusra Amanda; Likdanawati; Ibrahim Qamarius; Sullaida (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of employee experience, employee engagement, and work-life balance on employee performance at PT Pupuk Iskandar Muda. The background of this study is based on the importance of human resources as a strategic asset of the company, where employee performance is a key factor in achieving organizational goals. In practice, PT PIM faces several internal challenges such as lack of work experience among some employees, low employee engagement in work, and imbalance between work and personal life. This study uses a quantitative approach with a survey method through a questionnaire distributed to 103 respondents, which was determined by purposive sampling technique. The variables studied consist of employee experience, employee engagement, work-life balance as independent variables, and employee performance as the dependent variable. The results of this study are expected to provide an understanding of the factors that influence employee performance, as well as become a consideration in making human resource management policies at PT PIM in order to improve employee work effectiveness. This study also provides theoretical and practical contributions, both to the development of management science and the implementation of HR management strategies in organizations.